Amorphous metal–organic frameworks obtained from a crystalline precursor for the capture of iodine with high capacities. Issue 32 (1st April 2022) - Feng, Ying; Zou, Ming-Yan; Hu, Hao-Chen; Li, Wan-Han; Cai, Song-Liang; Zhang, Wei-Guang; Zheng, Sheng-Run
Abstract : Two amorphous metal–organic frameworks ( a MOFs) were obtained from a crystalline Co-MOF (SCNU-Z6) precursor and exhibited high iodine uptake capacities. Abstract : Two amorphous metal–organic frameworks ( a MOFs) were obtained from crystalline Co-MOF (SCNU-Z6) via temperature-induced ( a T -SCNU-Z6) and water-immersed ( a W -SCNU-Z6) approaches. They exhibited high iodine uptake, with the adsorption capacities of a T -SCNU-Z6 and a W -SCNU-Z6 reaching 2.05 and 5.04 g g −1, respectively. This work is the first report of iodine uptake by a MOFs.